Influence of the implementation of strengths-based nursing and healthcare on early childhood nurses' competencies: a mixed-method study - Camille Thentz; Christine Durgnat-Sciboz; Sylvie Macé; Marie-Catherine Béguin; Vincent Falcy; Elisabeth Schobinger; Gora Da Rocha (BMC, 2022)
Abstract Background The scope of practice for nurses caring for families has evolved to meet the challenges presented by societal changes and increasing needs. In 2015, early childhood nurses from a Swiss region decided to implement a new model of care to guide their practice. The aim of this study was to explore the changes to early childhood nurses' practices following the implementation of the strengths-based nursing and healthcare (SBNH) approach to care. Methods This study of early childhood nurses' (N = 61) practices used a pre-post intervention design and a mixed-method approach. Nurses' competencies and changes in practice were measured using the Nurse Competence Scale (NCS). The quantitative data were analysed using descriptive statistics, Kruskal Wallis tests and logistic regression. Thematic analysis was used to derive themes from the qualitative data. Results After the intervention, frequency of competency use increased in all domains of the NCS except the "teaching-coaching" domain; perceived levels of competencies also increased in all areas except "helping role" and "diagnostic functions". Age and length of employment at the current post hindered improvement in the "teaching-coaching" competency. Interviews revealed themes related to the implementation process: "adaptability", "implementation process", "ambivalence" and "engagement to change". Other themes were related to practice changes: "developing a disciplinary identity", "path with families" and "strengths". Conclusion This study showed that the use of perceived competencies changed over time after the introduction of SBNH into practice. Nurses questioned and adapted their routines based on SBNH. Nurse's vision of care also changed; they felt that their care was congruent with their values. For families, this approach allowed a change of vision with a resource-centred approach. Implementation of models of care such as the SBNH in the early childhood context is innovative, as little research in the literature addresses the early childhood community home-visiting context is still modest. This research underlines the added value of this approach on early childhood nurses' competencies.